Distal pathologies of the second molar in the presence of the mandibular third molar: Study by panoramic radiography - Mamadou Lamine Ndiaye; Binetou Catherine Gassama; Seydina Ousmane Niang; Papa Abdou Lecor; Aminata Ndiaye; Babacar Toure (Elsevier, 2021)
Objective: The aim of this study was to determine the frequency of dental caries and distal alveolysis of the mandibular second molar, associated with the presence of the third molar. Materials and methods: The study was carried out on digital panoramic X-rays of Senegalese subjects. The variables studied were the topographical anatomy of the left mandibular third molar and the presence of caries and alveolysis distal to the mandibular second molar. Statistical analysis was performed using the Jamovi software. Results: A total of 386 panoramic radiographs of 201 women (52%) and 185 men (48%) were retained. The average age was 45 ± 8 years. According to the status of the left mandibular third molar, 77.1% (n = 297) were in normal position and 22.9% (n = 88) were enclaved. Distal alveolysis of the second molar was found in 64.5% (n = 249) of the radiographs. Almost 50% of the second molars had caries in the presence of the enclaved third molar (p < 0,000). Lysis of the alveolar bone distal to 37 was noted in 42.7% (n = 38) cases associated with the enclaved third molar (p < 0,000). The prevalence of decayed second molars in the presence of the enclaved third molar in the horizontal position was 51.5% (n = 17). Conclusion: The presence of caries and alveolysis distal to the second molar was statistically associated with the presence of the impacted third molar.